2020
DOI: 10.1002/cjce.23691
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical water oxidation treatment of humic acid as a model organic compound of landfill leachate

Abstract: Landfill leachate is a complex and variable effluent, rich in organic and inorganic matters resistant to decomposition, and is an extreme pollutant. Humic acids (HA) are some of the most refractive substances in the leachates, which is the reason why they have been used as an organic model. The degradation of an HA solution through supercritical water oxidation (ScWO) was evaluated under a constant pressure of 22.5 MPa, temperatures from 400°C to 600°C, and reaction times from 15 to 60 seconds. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that photocatalysis can remove 61% to 85% of COD and 52% of phthalates in leachate (Azadi et al, 2021;Eslami et al, 2021). AOPs, specifically using supercritical water oxidation (ScWO) as a reagent, can remove 96% of phosphorus, 70% of nitrate, 94% of total dissolved solids, and 87% of true colour (Martins et al, 2020). EO can effectively remove 68% of COD and 40% of total organic carbon (Yan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that photocatalysis can remove 61% to 85% of COD and 52% of phthalates in leachate (Azadi et al, 2021;Eslami et al, 2021). AOPs, specifically using supercritical water oxidation (ScWO) as a reagent, can remove 96% of phosphorus, 70% of nitrate, 94% of total dissolved solids, and 87% of true colour (Martins et al, 2020). EO can effectively remove 68% of COD and 40% of total organic carbon (Yan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Subcritical water catalytic oxidation [74], supercritical water oxidation [75], and catalyzed wet oxidation [76] also demonstrated efficiency in the treatment of leachate UVQS, showing 66, 61, and 93% of HA removal, respectively. The elevated chemical cost generally restricts the possible use of these treatments [19].…”
Section: Chemical Treatmentsmentioning
confidence: 97%